Numerical analysis and experimental study on aerodynamic shape of support structure considering wind tunnel flow quality - Yi Zhang; Yangyi Xiao; Bo Xiong; Cunyuan Zhang; Yongtao Yin; Shaojie Pan; Xinfu Luo (Advances in Mechanical Engineering)
Aircraft continuously change their flight attitudes during actual operations. If a constant attitude is maintained during wind tunnel tests, the aerodynamic characteristics obtained may significantly deviate from the actual performance of the aircraft. Such discrepancies hinder the optimal design of aircraft and can adversely affect safety. The dual-rotating shaft mechanism is a commonly used model support system in wind tunnel testing, playing a crucial role in simulating various flight attitudes of the aircraft. The paper integrates the structural characteristics of a newly designed dual rotating shaft mechanism to perform a numerical analysis of its aerodynamic shape and evaluate its impact on the quality of the wind tunnel flow field. Multiple rounds of numerical simulations and comparative analyses were carried out on mechanisms with different structural configurations, leading to an optimized structural design. Subsequently, corresponding experiments were conducted to validate the design results. The results indicate that reducing the axial width and thickness of the front shaft crutch arm and positioning it further from the rotor center can alleviate upstream interference. The research provides a valuable reference for the future development of dual rotating shaft mechanisms.